Pengaruh Kompetensi, Akuntabilitas dan Peran Pendamping Desa Terhadap Pengelolaan Dana Desa - Luh Putri Persika Dewi; Gusti Ayu Rencana Sari Dewi (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2021)
The village is a small part of the country that is able to participate in the progress of the state and the government aims to prosper the community. Therefore, the development of the country, all certain activities will be given a budget by the government for the community in the form of village funds. This study aims to determine the effect of competence, accountability and the role of village facilitators on village fund management. This research uses quantitative methods. Data obtained through the distribution of questionnaires and measured on a Likert scale. The population and sample of this study were 43 village assistants and local village facilitators. Data analysis techniques used multiple linear regression analysis with the help of SPS version 20. The results of this study indicate that the variables of competency (X1), accountability (X2) and the role of village facilitators (X3) each have a positive and significant influence on village fund management